2016
DOI: 10.1111/nicc.12273
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge level of nurses in Jordan on ventilator‐associated pneumonia and preventive measures

Abstract: Hospital and nursing administrators should be actively involved in educational programmes and in assuring support for continuing education. Protocol for ventilator-associated pneumonia prevention should be developed based on current evidence-based guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
(33 reference statements)
1
36
0
3
Order By: Relevance
“…Studies reported several factors that contribute to the high rate of VAP in Jordanian hospitals in comparison with hospitals in the other developed countries. Such factors include lack of education and training for nurses (Hassan and Wahsheh, ), lack of resources and staff (Al‐Rawajfah et al, ), inadequate administration of antibiotics (Samrah et al, ), and poor compliance with infection control policies among nurses (Al‐Rawajfah, ). The findings from this study were consistent with those of Jahansefat et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies reported several factors that contribute to the high rate of VAP in Jordanian hospitals in comparison with hospitals in the other developed countries. Such factors include lack of education and training for nurses (Hassan and Wahsheh, ), lack of resources and staff (Al‐Rawajfah et al, ), inadequate administration of antibiotics (Samrah et al, ), and poor compliance with infection control policies among nurses (Al‐Rawajfah, ). The findings from this study were consistent with those of Jahansefat et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Jordan, Samrah et al (2016) revealed VAP-related mortality at 53%. Several factors have been implicated in the high rate of VAP such as lack of knowledge among nurses (Hassan and Wahsheh, 2016), delay in the administration of antibiotics (Samrah et al, 2016) and hospital overcrowding (Yepez et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it is emphasized that training health workers, especially nurses, in VAP interventions, and increasing their level of knowledge on this subject, play very important roles [13][14][15]. It is reported, however, that intensive care nurses have low-level or moderate awareness, knowledge, attitude, and harmony about evidence-based practices to prevent VAP [12,[16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite evidence‐based guidelines (Álvarez Lerma et al, ; Tablan et al, ), the application of these measures remains inadequate, and various studies show heterogeneous practices and insufficient compliance with the guidelines (Akın Korhan et al, ; Jansson et al, ; Lawrence and Fulbrook , ). Among the reasons that nurses report for failing to apply scientific evidence in their practice are routine‐based, rather than evidence‐based, working arrangements, lack of knowledge, demotivation, lack of time, excessive workloads and aspects related to the working environment and organizational structure of the system (Ali et al, ; Hassan and Wahsheh, ; Hugonnet et al, ; Jansson et al, ; Stone et al, ). Training is essential for the application of the guidelines, and it is related to most factors involved in the failure to comply.…”
Section: Introductionmentioning
confidence: 99%